Zirconium Tetrakis(8-hydroxyquinolinolate) and Lithium Schiff-Base Cluster Complex for Efficient Charge Injection and Transfer in Green PHOLED processed by OVPD. (4th June 2018) - Simkus, Gintautas; Pfeiffer, Pascal; Sanders, Simon; Stümmler, Dominik; Baumann, Peter K.; Surendrakumar, Sivagnansundram; Kumaraverl, Muttulingam; Liu, Maxson; Ravichandran, Seenivasagam; Kathirgamanathan, Poopathy; Vescan, Andrei; Kalisch, Holger; et al.
ABSTRACT: Typical electron transport (2, 2′, 2″-(1, 3, 5-benzinetriyl)-tris(1-phenyl-1-H-benzimidazole) (TPBi)) and injection (Cs2 CO3 ) materials are successfully replaced by zirconium tetrakis(8-hydroxyquinolinolate) (Zrq4 ) and lithium 2-((o-tolylimino)methyl)-phenolate (EI-111) in simplified OLED (organic light-emitting diodes) processed by organic vapor phase deposition (OVPD). The performance of combining Zrq4 and EI-111 is analyzed in unipolar devices and compared to devices with configurations of Zrq4 /Cs2 CO3, TPBi/EI-111 and TPBi/Cs2 CO3 . Current density-voltage (J-V) measurements are performed and correlated to different carrier injection and transport properties. The investigated material combinations are implemented in the simplified OLED structures and compared to each other. To account for the high HOMO level of Zrq4, 5 nm of TPBi are added to confine holes and excitons in the emissive layer (EML) and to improve device performance. After tailoring the organic stack for OLED with Zrq4, a remarkable boost in device efficiency is observed. The luminous efficacy increased from 3.0 to 21.9 lm/W and the EQE from 2.1 to 11.0 % for a device with Zrq4 /EI-111. Furthermore, OLED having Zrq4 /Cs2 CO3 show an even greater enhancement to 26.3 lm/W and 11.7 %.